Impelentasi Fissure Sealant dalam Pemecahan Karies Gigi pada Anak Usia Sekolah di UPT SPF SD Negeri Pampang II - Febi Magfirah; Aisyah AR; Siti Alfah; Aminah Mawahda; Indrayeni Olivia Putri Nur (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Introduction:. Dental caries is one of the most common oral health problems experienced by school-age children. A high prevalence of caries can affect growth and development, nutritional intake, and academic performance. One effective measure to prevent caries is the application of fissure sealants on posterior teeth.Objective:To implement fissure sealants for the prevention of dental caries and to improve students’ knowledge about oral health.Methods:The activities included initial dental examination, oral health education, application of fissure sealants, and evaluation of knowledge through pre-test and post-test among 35 fifth-grade students at UPT SPF SD Negeri Pampang II.Results:The findings showed that 30 students (85.7%) had deep pits and fissures, while 5 students (14.3%) had early caries. After the education session, students with good knowledge increased from 8 students (22.9%) to 27 students (77.1%). All students who met the indications successfully received fissure sealant treatment without complications.Conclusion: The implementation of fissure sealants is effective as a simple preventive measure in preventing dental caries among school-age children and enhances students’ awareness and knowledge of oral health. This program is recommended to be conducted regularly to reduce the risk of caries